Burnout in Pharmacy professionals during COVID-19 outbreak - Coelho , Eduarda; Amaral, Ana Paula; Rocha, Clara; Cruz, Rui; Brito-Costa, Sónia (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: COVID-19 pandemic has had a significant global impact on the economic, social, and public health sectors. The most severe consequences were felt firsthand in health systems and by their professionals, exposing them to greater physical and mental health risks, which need to be properly evaluated.  This study aims to assess burnout levels in pharmacy professionals in the context of the COVID-19 pandemic. Methods:  We collected data (N = 250), from pharmacy professionals (mean age of 34.24 years) (SD=8.99) who worked in different areas during the pandemic period using the Burnout Copenhagen Burnout Inventory (CBI). Results: There was an increase in weekly working hours after the onset of the COVID-19 pandemic and a decrease in the number of rest days per month. Most participants believe that their health status after the start of the pandemic is a little worse (44.4%). According to the CBI, the dimension with the highest average value of the Burnout subscale is related to the customer/user dimension (53.07), followed by the Work (44.60) and Personal (44.22) dimension. Conclusions: The levels of Burnout of pharmacy professionals are more accentuated in the Burnout dimension related to the client/user and the average values ​​of the various Burnout subscales are higher in Pharmacy Technicians than in Pharmacists.